Impact of main idiosyncratic and exogenous factors on cost Efficiency: The case of MENA banking industries - SFA approach - Samar Rizk (Financial Markets, Institutions and Risks)
This study explores the impact of main idiosyncratic endogenous (Capital ratio, Diversification, Liquidity, Return on equity (ROE), Banks assets’ size) and macroeconomic exogenous (Inflation rate, GDP growth rate and HHI concentration index) determinants of the banking firm that influence banks’ cost efficiency. Using the SFA (Stochastic Frontier Approach) we estimate cost efficiency of the MENA banking sectors through a two-stage model: i) Including idiosyncratic and macroeconomic factors at a first stage under SFAW (SFA With) and ii) excluding these factors under SFAWO (SFA without) at a second stage. By using this method, SFAW versus SFAWO, we compare between the efficiency frontiers and scores obtained and understand the effect of the integration of main determinants on efficiency of banks in the MENA region. Using a sample of 240 observations for MENA banks collected from 18 banking sectors, we analyze whether these criteria had impact on cost efficiency throughout 1999-2017. We find that SFAW scores of efficiency are higher than SFAWO. Furthermore, our results show clearly the impact of determinants selected on cost efficiency frontier. Finally, notwithstanding ongoing fundamental changes in MENA’s banking industries, the empirical results, show that these inefficiencies can be explained by the idiosyncratic factors (Assets ‘size, liquidity, profitability, etc.) which are under the control of bank managers and the macroeconomic environment (economic growth, inflation) which largely depends on the economic, monetary and financial policies adopted in each country of the MENA region.